STUDI KASUS TENTANG KESULITAN BERINTERAKSI SOSIAL PADA SISWA DI SMA NEGERI 7 PONTIANAK - Tiwi Oktavianti; Yuline; Elli Yanti (STKIP Subang, 2026)
The purpose of this study was to explore in depth the difficulties in social interaction experienced by students at Pontianak State Senior High School 7. This study used a descriptive method with a qualitative approach in the form of a case study. Data were obtained through interviews, observations, and documentation involving case subjects, guidance and counseling teachers, homeroom teachers, and peers. Data analysis was conducted through the stages of case identification, diagnosis, prognosis, treatment, evaluation, and follow-up. The focus of this study was to understand the symptoms, causal factors, impacts, and alternative support options to help students build more positive social relationships. The results of the study showed that students experiencing difficulties in social interaction tended to be quiet, waiting for others to invite them to speak, withdrawing, and exhibiting anxiety in social situations. After receiving guidance and counseling services using a behavioral counseling approach, students showed positive changes such as increased self-confidence, courage to interact, and improved communication skills with peers and teachers.